Restaurant English : (Tổng hợp, 2010)
The focus of Restaurant English is on listening and speaking to help learners develop the skills they need to effectively provide great service in English. In addition, the book contains introductory activities, vocabulary sections, focused grammar practice, and communicative functional exercises to familiarize students with how restaurant staff and guests interact.